COMPARISON OF COGNITIVE FUNCTION AND DEPRESSIVE SYMPTOMS IN INSTITUTIONALIZED HEALTHY AND OLDER PERSON WITH ALZHEIMER’S DISEASE - Carla M. Teixeira; Ana Filipa Pinto (PsychTech & Health Journal)
Physical activity shows benefits in cognitive function and the prevention and treatment of depression in older adults with Alzheimer’s disease and healthy ones. So, the purpose of this study was to compare cognitive function and depressive symptoms in two groups: a group of older adults with Alzheimer’s disease and a group of older adults without neurodegenerative diseases, by sex and level of physical activity. The sample was 30 participants divided into two groups: 15 participants with Alzheimer’s disease and 15 participants without neurodegenerative diseases. The instruments used were the Geriatric Depression Scale (GDS) and Mini-Mental State Examination (MMSE). The results revealed that older persons with Alzheimer’s disease exhibit a more significant impairment of cognitive skills (p = .001) and a higher incidence of depressive symptoms (p = .001) compared to older persons without neurodegenerative diseases, with no differences between sex (p > .05). Results show that active older person had higher scores in cognitive abilities (p = .001) and a lower incidence of depression (p = .001). It seems that Alzheimer’s disease, typically associated with cognitive abilities decline and incidence of depressive symptoms, and physical activity influence cognitive performance and depressive symptoms in older people with Alzheimer’s disease and without dementia.